(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the anatomical characteristics of the arterial blood supply to the colon in Vietnamese cadavers, including origin, branching, and anastomoses, while documenting rare anatomical variants. Method: A cross-sectional descriptive study was conducted on 32 formalin-fixed Vietnamese adult cadavers (20 males, 12 females) at the Department of Anatomy, University of Medicine and Pharmacy, Ho Chi Minh City. Dissection was performed to assess the origin, diameter, length, number of lateral branches, and anastomoses of the superior mesenteric artery and inferior mesenteric artery. Structures such as the marginal artery of Drummond, Riolan’s arch, and Moskowitz’s meandering artery were also evaluated. Results: The mean colon length was 114.60 ± 16.15 cm. The superior mesenteric artery originated predominantly at the middle and lower third of L1 (37.5% and 43.75%), with a diameter of 7.45 ± 1.04 mm and 2-5 lateral branches. The inferior mesenteric artery originated at the middle and lower third of L3 (25% and 43.75%), with a diameter of 2.72 ± 0.65 mm and 2-3 lateral branches. The marginal artery of Drummond was present in 100% of specimens, Riolan’s arch in 37.5%, and Moskowitz’s meandering artery in 6.25%. A rare case of the middle mesenteric artery was identified, originating directly from the abdominal aorta, supplying the transverse colon and splenic flexure. Conclusion: The arterial blood supply to the colon in Vietnamese individuals exhibits significant variability in origin, branching, anastomoses and a novel report of the middle mesenteric artery. These findings have important implications for colorectal surgery and diagnostic imaging.